KARAKTERISTIK PERIZINAN BERUSAHA BERDASARKAN UU NOMOR 6 TAHUN 2023 TENTANG PENETAPAN PERPU NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA MENJADI UNDANG-UNDANG - Bagus Oktafian Abrianto; Samuel Dharma Putra Nainggolan (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2023)
Licensing is a spirit of administrative law that studies law in a moving state. Licensing is required for the running of a government, both central government and regional government. Based on the principle of decentralization, regional governments are allowed to regulate their own areas and for this reason permits are issued by the regional government. In practice, there is a lot of overlapping and overlapping regarding licensing between the central government and regional governments both in terms of substance and technical implementation in each existing Regional Work Unit (SKPD), the enactment of Law Number 6 of 2023 concerning the Determination of Replacement Government Regulations Law Number 2 of 2022 concerning Job Creation Becomes a Law changing the licensing constellation in Indonesia. In the area licensing is attempted to be carried out through a service system implemented by Online Single Submission (OSS) and One Stop Integrated Service (PTSPP), both of which must be integrated with OSS. Licensing services in areas that are integrated with or PTSP are the focus of this research study. This research is normative legal research that uses a statutory approach and a conceptual approach that will be used to answer existing legal issues.